2009
DOI: 10.1152/physiolgenomics.00017.2009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of the junctophilin gene family

Abstract: Junctophilins (JPHs) are members of a junctional membrane complex protein family important for the physical approximation of plasmalemmal and sarcoplasmic/endoplasmic reticulum membranes. As such, JPHs facilitate signal transduction in excitable cells between plasmalemmal voltagegated calcium channels and intracellular calcium release channels. To determine the molecular evolution of the JPH gene family, we performed a phylogenetic analysis of over 60 JPH genes from over 40 species and compared conservation ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 55 publications
3
103
0
Order By: Relevance
“…S3). These findings suggest that, similar to Stim1, Stim2, junctionphilins and Ist2p (Deng et al, 2009;Ercan et al, 2009;Fischer et al, 2009;Garbino et al, 2009;Lewis, 2007;Wu et al, 2006), the TMD of Tcb2p is in the ER and its cytosolic domains binds the PM, causing it to be enriched at ER-PM contact sites.…”
Section: Tricalbins Localize To Er-pm Contact Sitesmentioning
confidence: 85%
“…S3). These findings suggest that, similar to Stim1, Stim2, junctionphilins and Ist2p (Deng et al, 2009;Ercan et al, 2009;Fischer et al, 2009;Garbino et al, 2009;Lewis, 2007;Wu et al, 2006), the TMD of Tcb2p is in the ER and its cytosolic domains binds the PM, causing it to be enriched at ER-PM contact sites.…”
Section: Tricalbins Localize To Er-pm Contact Sitesmentioning
confidence: 85%
“…For example, SETD7 is recruited to the promoters of target genes by interacting with transcription factors such as NFκB (20). Secondly, SETD7 is the only methyltransferase that contains membrane occupation and recognition nexus (MORN) repeats that are found in proteins linking the membrane to the cytoskeleton (22). This observation suggests a potential cytoplasmic role for SETD7.…”
Section: Significancementioning
confidence: 99%
“…Junctophilins contain eight repeats of the membrane occupation and recognition nexus (MORN) motifs that bind to phospholipids in the N terminus and a C-terminal ER membrane-spanning transmembrane segment (20,22). In this study, we observed expression of JP4 in both human and mouse T cells, which was further enhanced by TCR stimulation.…”
mentioning
confidence: 71%